Biogeography-based interference mitigation scheme for ofdma system in heterogeneous network - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Hassan Abdalla Hashim, Aisha; Hashim, Wahidah; Islam, Shayla (Science & Engineering Research Support soCiety, Republic of Korea, 2016)
In Heterogeneous Network (HetNet), the small base station such as femtocells are deployed in indoor and multiple business complexes in order to extend the coverage and capacity. The deployment of co-channel (i.e. shared channel) for femtocells along with macrocell induces the severe interference issues. This is because of effects on SINR and thereby capacity become deteriorated. Therefore, this paper investigates the interference mitigation techniques and come out with a proposal to improve the Signal to Interference Noise Ratio (SINR) performance as well as total capacity in Heterogeneous Network (HetNet).The simulation results show that the achieved capacity is maximized than the existing technique.